2018
DOI: 10.1021/acs.jpcc.8b08924
|View full text |Cite
|
Sign up to set email alerts
|

Simple Route to Metal cyclo-N5 Salt: High-Pressure Synthesis of CuN5

Abstract: A naked cyclo-N5 – salt has yet to be recovered to ambient conditions, precluding its application as a high-energy density material for explosive or propulsion applications. Here, we suggest a simple route for the synthesis of a metal cyclo-N5 – salt via compressing CuN6. Using first-principles calculations with structural search, we predict a CuN5 compound with a cyclo-N5 – anion that is energetically favorite in the pressure range of 50–100 GPa. At ambient conditions, CuN5 comprises alternant-connected cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…[ 104,105 ] Three possible bonding modes were proposed, i.e., monodentate, bidentate, and metallocene‐like coordination. Recent first‐principles calculations combined with modern structure search algorithms have predicted a rich variety of crystal structures, such as in MN 5 (M = H, Na, and Cu), [ 30,34,106 ] MN 10 (M = Be, Ca, Mg, Ba, and Zn), [ 33,107–109 ] MN 15 (M = Al, Ga, Sc, and Y), [ 110 ] and IrN x ( x = 4, 7), [ 111 ] and estimated the synthesis conditions and energetic performance for many. These studies are critical, as they often serve to guide the experimental exploration of new materials, such as in the case of LiN 5 and CsN 5 .…”
Section: Nitrogen‐rich Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 104,105 ] Three possible bonding modes were proposed, i.e., monodentate, bidentate, and metallocene‐like coordination. Recent first‐principles calculations combined with modern structure search algorithms have predicted a rich variety of crystal structures, such as in MN 5 (M = H, Na, and Cu), [ 30,34,106 ] MN 10 (M = Be, Ca, Mg, Ba, and Zn), [ 33,107–109 ] MN 15 (M = Al, Ga, Sc, and Y), [ 110 ] and IrN x ( x = 4, 7), [ 111 ] and estimated the synthesis conditions and energetic performance for many. These studies are critical, as they often serve to guide the experimental exploration of new materials, such as in the case of LiN 5 and CsN 5 .…”
Section: Nitrogen‐rich Compoundsmentioning
confidence: 99%
“…In contrast to the extreme difficulty of isolating N 5 − at room conditions, studies have shown that N 5 − can be stabilized at high pressure in compounds such as LiN 5 , [ 29 ] NaN 5 , [ 30 ] CsN 5 , [ 31,32 ] MgN 10 , [ 33 ] and CuN 5 . [ 34 ] Moreover, N 5 3− is predicted to further aggregate and form higher oligomers or polymeric network in GaN 5 and GaN 6 . [ 35 ] In 2018, Laniel et al successfully synthesized LiN 5 at high pressure and retrieved the product down to ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers at the University of South Florida successfully synthesized a solid compound consisting of the isolated pentazolate anion N 5 − , which was obtained by compressing and laser heating a mixture of cesium azide (CsN 3 ) and N 2 cryogenic liquid in DAC. 5 Inspired by this research, some naked cyclic N 5 − salts were designed, such as CuN 5 , 102 and Ibam-ZnN 4 are 2 kJ g −1 and 2.3 kJ g −1 , respectively, and their stable pressure ranges are 16.9-91.39 GPa and 91.39-100 GPa, respectively. 108 It must be pointed out that the LiN 5 compound is not only the first environmentally stable pentazo salt synthesized under high pressure, but also the poly-nitrogen compound with the highest nitrogen content at room temperature.…”
Section: High-energy-density Materialsmentioning
confidence: 99%
“…Significantly, cyclo ‐N 5 − was successfully stabilized and crystallographically characterized in the (N 5 ) 6 (H 3 O) 3 (NH 4 ) 4 Cl salt form in 2017, and further captured by forming stable metal pentazolate hydrate complexes or in the three‐dimensional (3D) metal‐pentazolate frameworks . These fascinating theoretical and experimental achievements strongly demonstrated that cyclo ‐N 5 − is aromatic and completely accessible …”
Section: Introductionmentioning
confidence: 98%
“…[10][11][12][13] These fascinating theoretical and experimental achievements strongly demonstrated that cyclo-N 5 − is aromatic and completely accessible. [14,15] Polyphosphorus monocycles also attracted extensive interest. Theoretical calculations suggested that the pentaphosphole ion cyclo-P 5 − is aromatic and stable toward dissociation.…”
mentioning
confidence: 99%